A simple route to synchronized nucleation of self-catalyzed GaAs nanowires on silicon for sub-Poissonian length distributions. (12th October 2018) - Tauchnitz, Tina; Berdnikov, Yury; Dubrovskii, Vladimir G; Schneider, Harald; Helm, Manfred; Dimakis, Emmanouil
Abstract: We demonstrate a simple route to grow ensembles of self-catalyzed GaAs nanowires with a remarkably narrow statistical distribution of lengths on natively oxidized Si(111) substrates. The fitting of the nanowire length distribution (LD) with a theoretical model reveals that the key requirements for narrow LDs are the synchronized nucleation of all nanowires on the substrate and the absence of beam shadowing from adjacent nanowires. Both requirements are fulfilled by controlling the size and number density of the openings in SiO x, where the nanowires nucleate. This is achieved by using a pre-growth treatment of the substrate with Ga droplets and two annealing cycles. The narrowest nanowire LDs are markedly sub-Poissonian, which validates the theoretical predictions about temporally anti-correlated nucleation events in individual nanowires, the so-called nucleation antibunching. Finally, the reproducibility of sub-Poissonian LDs attests the reliability of our growth method.